1983
DOI: 10.2337/diab.32.9.876
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glucose Concentrations Increase Factor VIIIR:Ag Levels in Human Umbilical Vein Endothelial Cells

Abstract: To determine if endothelial cell metabolism is affected by the elevated glucose concentrations known to occur in diabetes mellitus, we measured cellular Factor VIIIR:Ag in endothelial cells grown under conditions of increased glucose concentration. The results of this study illustrate that, under cell culture conditions, an increase in glucose concentration results in increased cellular levels of Factor VIIIR:Ag. Specifically, a glucose concentration of 300 mg/dl resulted in a 23% increase in Factor VIIIR:Ag l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…How, then, may the changes in plasma vWF levels observed in our patients, who had normal urinary albumin excretion, be explained? vWF levels may be influenced by age [23] and, possibly, by glycaemic control [16,17,24], but, as these factors were similar in patients with and without increases in plasma vWF, they are an unlikely explanation for the differences in vWF level changes observed. As diabetic nephropathy is associated with both high vWF concentrations and a high incidence of cardiovascular disease [3-5, 15, 16], and as atherosclerosis in non-diabetic patients is also associated with high vWF levels [25,26], we propose that diabetic patients with normal urinary albumin excretion and high or increasing vWF levels have clinically silent endothelial dysfunction, which may indicate an increased risk of developing nephropathy and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…How, then, may the changes in plasma vWF levels observed in our patients, who had normal urinary albumin excretion, be explained? vWF levels may be influenced by age [23] and, possibly, by glycaemic control [16,17,24], but, as these factors were similar in patients with and without increases in plasma vWF, they are an unlikely explanation for the differences in vWF level changes observed. As diabetic nephropathy is associated with both high vWF concentrations and a high incidence of cardiovascular disease [3-5, 15, 16], and as atherosclerosis in non-diabetic patients is also associated with high vWF levels [25,26], we propose that diabetic patients with normal urinary albumin excretion and high or increasing vWF levels have clinically silent endothelial dysfunction, which may indicate an increased risk of developing nephropathy and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether the clearance of vWF is also affected by diabetic microangiopathy, nor what causes endothelial cells to produce more vWF. A study in vitro had reported increased intracellular content of vWF in cultured endothelium subjected to glucose concentrations mimicking those found in poorly-controlled patients [113].…”
Section: Haemostasismentioning
confidence: 94%
“…As a glucose-independent control, 3-actin was used. Beside connective tissue proteins, these target molecules can be components of the clotting system like the von Willebrand Factor, which is regulated by glucose (Mordes et al, 1983), or possibly adhesion molecules like ICAM-1 (Simmons et al, 1988). In the latter case, a direct glucose regulation was not observed up to now but there is some evidence that adhesion molecule-triggered monocyte binding to endothelial cells is increased by glucose (Kim et al, 1994).…”
Section: Discussionmentioning
confidence: 99%